The Benefits of Telehealth on Quality of Life of People Living with Type 2 Diabetes Mellitus: A Literature Review - Jannah, Fitriatul; Safutra Suraya, Andi; Erindia, Firnanda; Nurwahidah, Nurwahidah; Chayatush Sholichah, Ahla (Fundamental and Management Nursing Journal, 2023)
Introduction: Advancement technology and information benefit societies by way telehealth access, including those with diabetes mellitus. Telehealth implementation in diabetes mellitus management is a great solution of increasing access to healthcare and reducing geographical inequalities. Nevertheless, the effectiveness of service among people living with diabetes remains inconsistant. This review aims to summarize and evaluate the evidence on the effectiveness of telehealth on quality of life in type 2 diabetes mellitus Method: This review considers the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) guideline. The results reported in descriptive narrative approach. The following databases; Scopus, Science Direct, PubMed, and Web of Science were comprehensively searched to find article from January, 1st 2018 to December 31st 2023. Inclusion was made to English and full-text article. Results: Two articles were included in the final review. A total of 482 type 2 DM patients were used telehealth. Findings on the impacts of the usability of telehealth on the QoL of Type 2 DM is telehealth relevant alternative to the care of DFU patients, with stable health, well-being and quality of life conditions and smartphone application-based interventions in the management of type 2 DM show that the quality of life in the following four dominants; psychological, social, environmental, and physical health revealed significant improvements Conclusions: Telehealth has good potential to be developed in the service of diabetes mellitus patients. The following internet-based delivered mode; web, and smartphones improve the quality of life and the well-being of patients with type 2 diabetes mellitus. However, lack of studies measuring the effectivity of telehealth among people with diabetes mellitus. Future development of internet-based interventions should further take into consideration the consolidated set of diabetes mellitus principles. Keyword: Type 2 Diabetes Mellitus, Quality of Life, Telehealth, Nursing Practice, Nursing Care